A Morphometric and Morphological Analysis of Plantaris in Fetal Cadavers - Aynur Çiçekcibaşı; Mustafa Büyükmumcu; Duygu Akın Saygın; Ahmet Safa Gökşan; Anil Didem Aydın Kabakçı (Genel Tıp Dergisi)
Objective: The plantaris is a muscle in the back of the leg that has a short body and a long, thin tendon. The muscle acts functionally with the gastrocnemius. Due to removal of the muscle does not cause a change in limb function, it is used as a potential source of graft. The aim of the present study was to investigate the morphological features and possible variations of plantaris in fetal cadavers.Methods: This study was carried out on the fetal cadaver collection of University of Necmettin Erbakan, Faculty of Medicine, Anatomy Department. 11 male and 9 female fetal cadavers (ages range: 28 to 40 weeks) were used. The muscle belly length (LB), width (WB) and thickness (TB) were measured. The plantaris insertion was classified into 4 types. Furtermore, the distal part of the tendon was classified as the fan-shaped and flat-shaped.Results: It was determined that plantaris was present in 36 of 40 (90%) lower extremities and absent in 4 (10%). The average muscle belly length (LB), width (WB) and thickness (TB) was found 13.29±3.73 mm, 4.72±1.77 mm and 3.65±1.17 mm, respectively. It was observed that the plantaris tendon often (Type 2, 67.5%) inserts in the anteromedial of the calcaneal tendon. Furthermore, the most common insertion type was observed as flat-shaped (86.11%). Conclusion: We believe that the data obtained from our study will be useful in procedures such as flexor tendinoplasties, reconstruction of hand tendons and lateral ankle ligaments, and repair of atrioventricular valves, which are planned to be performed in infancy and childhood.